2020
DOI: 10.1002/stem.3308
|View full text |Cite
|
Sign up to set email alerts
|

IRF7 suppresses hematopoietic regeneration under stress via CXCR4

Abstract: Hematopoietic stem cells (HSCs) maintain quiescence under steady state; however, they are compelled to proliferate and expand to replenish the blood system under stress. The molecular basis underlying stress hematopoiesis remains to be fully understood. In this study, we reported that IRF7 represents an important regulator of stress hematopoiesis. Interferon regulatory factor 7 (IRF7) was dispensable for normal hematopoiesis, whereas its deficiency significantly enhanced hematopoietic stem and progenitor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Additionally, IPA analysis revealed that the dual drug treatment led to a significant decrease in the expression of genes involved in inflammation ( Figure 3 B). Consistent with these findings, Irf7 (interferon regulatory factor 7), 32 a key transcriptional regulator of type I interferon (IFN)-dependent immune response, was significantly repressed in mutant cells treated with a combination of the two drugs ( Figure 3 C). Consistent with the observations made utilizing IPA, GSEA also revealed that GOF Shp2 E76K/+ mice treated with the dual drug combination resulted in decreased PI3Kinase signaling (NES: −1.99, p < 0.001), inositol phosphate metabolism (NES: −1.92, p < 0.001), BCR signaling pathway (NES: −1.67, p < 0.001), extracellular matrix interaction (NES: −2.17, p < 0.001), focal adhesion (NES: −2.02, p < 0.001), and actin cytoskeleton regulation (NES: −1.73, p < 0.001) ( Figure 3 D).…”
Section: Resultssupporting
confidence: 73%
“…Additionally, IPA analysis revealed that the dual drug treatment led to a significant decrease in the expression of genes involved in inflammation ( Figure 3 B). Consistent with these findings, Irf7 (interferon regulatory factor 7), 32 a key transcriptional regulator of type I interferon (IFN)-dependent immune response, was significantly repressed in mutant cells treated with a combination of the two drugs ( Figure 3 C). Consistent with the observations made utilizing IPA, GSEA also revealed that GOF Shp2 E76K/+ mice treated with the dual drug combination resulted in decreased PI3Kinase signaling (NES: −1.99, p < 0.001), inositol phosphate metabolism (NES: −1.92, p < 0.001), BCR signaling pathway (NES: −1.67, p < 0.001), extracellular matrix interaction (NES: −2.17, p < 0.001), focal adhesion (NES: −2.02, p < 0.001), and actin cytoskeleton regulation (NES: −1.73, p < 0.001) ( Figure 3 D).…”
Section: Resultssupporting
confidence: 73%
“…IRF7 has been implicated in tumor progression and microenvironment-related mechanisms have been proposed [ 16 , 31 ], while opposite intrinsic effects on tumor progression were reported in different tumors [ 17 , 18 ]. In hematopoiesis, IRF7 promotes the proliferation of HSCs under stress conditions [ 32 ]. Downregulation of IRF7 was detected in some AML cases with specific genetic abnormalities from Bloodspot.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have demonstrated the multifaceted roles of IRF7 in diseases by targeting downstream genes [ 19 , 56 ]. miR-375-3p upregulation is deemed to reduce the production of IL-1β and IL-6 in ECs in atopic dermatitis [ 57 ], and miR-375-3p upregulation in endothelial progenitor cells-isolated extracellular vesicles ameliorates sepsis in rats, as evidenced by alleviated pathological damage and decreased apoptosis, inflammatory responses, and oxidative stress in rat myocardial tissue [ 58 ], indicating the beneficial role of miR-375-3p in cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…IRF7, as a transcription factor, functions in disease by targeting downstream genes [ 19 ]. microRNAs (miRs), a subcategory of noncoding RNAs, affect gene expression at the post-transcriptional level by interacting with the target messenger RNAs (mRNAs) and act as regulators of cellular processes and animal development [ 20 ].…”
Section: Introductionmentioning
confidence: 99%